Handbook of semiconductor silicon technology - O'Mara, William C.; Herring, Robert B.; Hunt, Lee P. (Noyes Publications, 1990)
This book is an up-to-date summary of the science, technology and manufacturing of semiconductor silicon materials.
Keywords: Semiconductors -- Handbooks, manuals, etc.; Silicon crystals -- Handbooks, manuals, etc.; elektronické knihy; electronic books